VD_FINDINFO HC / 2013 / 12 vom 7. November 2012 - VD Tribunal cantonal (2012)
DÉPENS, MOYEN DE DROIT, DROIT TRANSITOIRE | 156 CPC, 110 CPC (CH), 319 let. a CPC (CH), 319 let. b ch. 1 CPC (CH), 404 al. 1 CPC (CH), 405 al. 1 CPC (CH), 95 al. 1 CPC (CH)